Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T17:29:33+01:00
A) 1,25y-8=0,25y+7 /-0,25y +8
y = 15


B) 2(2y-12)-8=16
4y-24-8 = 16
4y - 32 = 16 /+32
4y = 48 /:4
y = 12


C) z-14=z/3-z/9 /*9
9z-126 = 3z-z /+126
9z = 2z+126 /-2z
7z = 126 /:7
z = 18


D) 1/3x+5/3=x+1 /*3
x+5 = 3x+3 /-x -5
2x = -2 /:2
x = -1


E) 3x-7-x+5=6-x+1
2x-2 = 7-x /+x +2
3x = 9 /:3
x = 3


F) 6x+5=3x+32 /-3x -5
3x = 27 /:3
x = 9
1 5 1
2010-03-11T17:40:20+01:00
A) 1,25y - 8 = 0,25y + 7 | - 0,25y + 8
1,25y - 0,25y = 7 + 8
y = 15

b) 2 * (2y - 12) - 8 = 16
4y - 24 - 8 = 16
4y - 32 = 16 | + 32
4y = 16 + 32 | : 4
y = 48 : 4
y = 12

c) z - 14 = z/3 - z/9
z - 14 = 3z/9 - z/9
z - 14 = 2z/9 | * 9
9 * (z - 14) = 2z
9z - 126 = 2z | - 2z + 126
9z - 2z = 126
7z = 126
z = 18

d) 1/3x + 5/3 = x + 1 | - x - 5/3
1/3x - x = 1 - 5/3
-2/3x = -2/3 | : - 3/2
x = 1

e) 3x - 7 - x + 5 = 6 - x + 1
2x - 2 = 7 - x | + x + 2
2x + x = 7 + 2
3x = 9 | : 3
x = 3

f) 6x + 5 = 3x + 32 | -3x - 5
6x - 3x = 32 - 5
3x = 27 | : 3
x = 9
1 5 1